PENGHALANG SOSIAL DAN PSIKOLOGIS PADA PROYEK KONSTRUKSI DENGAN PRINSIP BANGUNAN HIJAU - Caesariadi, Tri Wibowo (Department of Architecture, Universitas Tanjungpura, 2015)
Proyek konstruksi bangunan merupakan kegiatan yang menentukan penerapan prinsip bangunan hijau. Gerakan bangunan hijau yang telah berlangsung cukup lama telah cukup berhasil secara teknologi dan ekonomis, namun halangan dapat datang dari manusia yang terlibat (stakeholders) pada proyek tersebut. Penghalang ini berangkat dari faktor sosial dan psikologis manusia, yang seringkali tidak disadari. Kajian tentang penghalang tersebut dilihat dari tingkat individu, organisasi dan kelembagaan. Pemecahan masalah dilakukan dengan melihat penghalang sebagai kesempatan atau sebagai masalah yang harus dipecahkan. Faktor edukasi memegang peranan penting dalam mengubah faktor sosial dan psikologis yang menghalangi tersebut. Termasuk pula peranan penting pemerintah sebagai pengatur Process of construction project is an activity which determines the application of the principles of green building. Green building movement has been going on for quite a while and has been significantly successful both technologically and economically. However, obstructions may come from humans involved (stakeholders) in the project. These obstructions originated from the social and psychological factors, which are often unrecognized. This study on the obstructions covered from the level of individuals, organizations and institutions. Problem solving is done by looking at the obstructions as the opportunity or as a problem to be solved. Education holds significant role in changing social and psychological factor, this includes the role of government as the regulatorREFERENCES______ 2008. A Guide to the Project Management Body of Knowledge (PMBOK® Guide) — Fourth Edition. Newtown Square: Project Manage-ment Institute.______ Green Building Council Indonesia. http://www.gbcindonesia.org. Akses: 7 Desember 2010.Hoffman, Andrew J. & Henn, Rebecca. 2008. Overcoming the Social and Psychological Barriers to Green Building. Organization and Environment, Vol. 21 number 4, December 2008. Sage Publications. http://oae.sagepub.com/content/21/4/ 390.refs.htmlRetzlaff, Rebecca C. 2009. The Use of LEED in Planning and Development Regulation: An Exploratory Analysis. Journal of Planning Education and Research, Vol. 29, May 2009. Sage Publications. http://jpe.sagepub.com/ content/ 29/1/67.refs.html